MONITORING AND EVALUATION SYSTEM OF SYIRKAH BSI SMART AGENT PROGRAMME: A STUDY IN BANDA ACEH CITY, INDONESIA - Ismuna, Rizalul Maula; Sulfanwandi; Muhammad Syafril (Centre for Adat and Legal Studies of Aceh Province (CeFALSAP), 2024)
Working capital financing is a financing facility provided to individuals, business entities and legal entities for working capital needs. Bank Syariah Indonesia (BSI) offers one of the products known as syirkah (partnership) financing. The purpose of this research is to find out the monitoring and evaluation system carried out by BSI on the BSI Smart Agent product. The results of this study indicate that the cooperation agreement between the agent and the BSI is a business realisation contract which initially the agent only runs his business according to the procedures given by the BSI. Then, BSI emphasises to the agent that the facilities and services are carried out according to the procedures set by BSI. The profit-sharing ratio agreed by both parties is that the agent directly benefits from the realisation of his business through revenue sharing with the same portion and the same value. Monitoring and evaluation conducted by BSI aims to ensure operational compliance with sharia principles and improve the efficiency and effectiveness of the services provided. The implementation of this system plays an important role in supporting Islamic financial inclusion and has a positive impact on the economic growth of the community.